Risk perception on needlestick injury and effectiveness of the needlestick prevention module among house officers in Kelantan - Kutubudin, Ahmed Farrasyah Mohd (2024)
Introduction: House officers (HOs) face a significant occupational threat from needlestick injuries (NSIs), posing potential risks of exposure to bloodborne pathogens. Understanding the factors influencing NSI risk perception and developing effective training modules are essential for implementing robust preventive measures. This research explores factors influencing NSI risk perception among HOs and evaluates the effectiveness of the Needlestick Injury Prevention Module (N-SIP) in enhancing NSI-related knowledge and risk perception. Objectives: The objectives of this study is to determine the mean perception score on risk of NSI, factors associated with mean the perception score, module development and validation, and effectiveness of the newly developed module. Methodology: This study utilized a cross-sectional design involving 176 HOs, who completed a self administered questionnaire. Linear regression identified associated factors of NSI risk perception scores. Additionally, the N-SIP module was developed using the ADDIE model and underwent content validation by experts and face validation by HOs. A non-randomised interventional design assigned HOs to either the intervention group receiving the N-SIP module or a control group, with NSI risk perception scores assessed at baseline, three weeks, and six weeks post-intervention